Analysis of the influence of karst cave parameters on surface settlement in TBM tunnelling - Dong, Bichang; Yang, Tao; Ju, Binbin; Qu, Zhongying; Yi, Chao (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
In order to study the influence of multiple karst cave factors on surface settlement during tunnel boring machine (referred to TBM hereinafter) tunnelling, a three-dimensional numerical model is built by taking a subway project as an example and combining it with MIDAS GTS NX finite element software. Secondly, the influence of the radius, height, angle, vertical net distance and horizontal distance of the karst cave on maximum surface settlement is studied and sorted under the two working conditions of treatment and lack of treatment using the gray correlation analysis method. Additionally, a multi-factor numerical model of the untreated karst cave is established. Finally, based on the preceding research, a multi-factor prediction model for maximum surface settlement is proposed and tested. The results reveal that when the karst cave is not treated, the radius and height of the karst cave have a significant effect on maximum surface settlement. Following cave treatment however, the influence of the cave parameters on maximum settlement of the surface is greatly reduced. The calculating model created in this study offers excellent prediction accuracy and good adaptability.